Ultrastructural studies of Euryale ferox leaf infected by Alternaria alternata - and S.C. SHARMA, A.K. DWIVEDI, RITA SHEKHAR (Indian Phytopathology, 2002)
Transmission electron microscopic studies of healthy and infected leaves of Euryale ferox Salisbury by Alternaria alternata (Fr.) Keissler demonstrated several post-infection changes at cellular level e.g. disruptions in the membrane system, reductionin size and change in the shape of chloroplast, alteration in organization of granal stacks in thylakoid and disappearance of starch reserves in the chloroplast. However, plastoglobuli remain prominent even at a much later stage. The infection tends to advance the ageing process and also results in chlorosis and finally necrosis of the cell.